Dysmotility in Esophageal Atresia: Pathophysiology, Characterization, and Treatment - Faure, Christophe; Righini Grunder, Franziska (Frontiers in Pediatrics, 2017)
Esophageal dysmotility is almost universal after esophageal atresia repair and is mainly related to the developmental anomaly of the esophagus. Esophageal dysmotility is involved in the pathophysiology of numerous symptoms and co-morbidities associated with esophageal atresia such as gastroesophageal reflux disease, aspiration and respiratory complications and symptoms of dysphagia and feeding disorders. High resolution esophageal manometry (HREM) has facilitated the characterization of the dysmotility but there is an incomplete correlation between symptoms and manometrical patterns. Impedance coupled to HREM should help to predict the clinical outcome and therefore personalize patient management. Nowadays, the management of esophageal dysmotility in patients with esophageal atresia is essentially based on treatment of associated inflammation related to peptic or eosinophilic esophagitis.